Automatic Image Self-Enhancement for Multi-Scale Spectral on Low Resolution Video - Arwin Halim; Sunaryo Winardi; Erlina Halim (Faculty of Computer Science - Universitas Indonesia, 2021)
MSR technique is a process used to reduce the search area in an image. MSR relies heavily on image salience from image capture devices. The purpose of this study is to improve the detection of people's objects on video by increasing the quality of the image frames on video and MSR. This research uses artificial video taken in a room installed by CCTV. Object detection is evaluated using precision, recall, and fscore values. The results showed an increase in the quality of the performance of object detection that was properly detected as a person. The average detection performance is indicated by an fscore of 14.47%. Increasing the quantity of detection of objects of people reached 168.8% compared to the detection of only using MSR